Compliance with IMF Program Indicators and Growth in Transition Economies - Unigovskaya, Anna (IMF Working Papers; Working Paper ;, 2000)
This paper makes use of the IMF's Database for Monitoring Fund Arrangements (MONA) to investigate whether transition countries that more successfully implement the conditionality of IMF programs tend to show a better performance on recovery and growth. It is not possible to determine a clear-cut relationship between the index that determines the level of compliance with structural benchmarks in IMF programs and growth. However, the paper finds a definite, positive relationship between the index of compliance with performance criteria and growth, even after controlling for the extent of stabilization of the transition countries.